1949
DOI: 10.2307/1364563
|View full text |Cite
|
Sign up to set email alerts
|

The Endemic Avifauna of Saipan, Tinian, Guam and Palau

Abstract: In the year from December, 1944, to December, 1945, I made a zoological collection, chiefly animals of medical interest, on the islands of Saipan, Tinian, Guam and Palau in Micronesia. These were obtained for the United States Army Medical Museum. Birds were collected incidentally to procuring a collection of mammals and their ectoparasites; they were turned over to the United States National Museum by the Army Medical Museum. Richard E. Genelly worked with me on Tinian and generously provided the photographs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
2

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 0 publications
1
43
2
Order By: Relevance
“…Food habits.-Foods previously reported for this species include black crickets (Seale 1901), grasshoppers, small fish (Marshall 1949), insects, and snails (Beaty 1967). Six stomachs examined by DAWR staff in 1968 and 1969, however, contained only small reptiles, including skinks, geckos, and anoles.…”
Section: Species Accounts Yellow Bittern (Ixobrychus Sinensis)mentioning
confidence: 97%
See 2 more Smart Citations
“…Food habits.-Foods previously reported for this species include black crickets (Seale 1901), grasshoppers, small fish (Marshall 1949), insects, and snails (Beaty 1967). Six stomachs examined by DAWR staff in 1968 and 1969, however, contained only small reptiles, including skinks, geckos, and anoles.…”
Section: Species Accounts Yellow Bittern (Ixobrychus Sinensis)mentioning
confidence: 97%
“…Marshall (1949) reported that G. canifrons from the Palau Islands is mainly terrestrial, and Mayr (1945) stated that terrestrial habits are common for Gallicolumba species. Marshall (1949) reported that G. canifrons from the Palau Islands is mainly terrestrial, and Mayr (1945) stated that terrestrial habits are common for Gallicolumba species.…”
Section: White-throatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous authors regarded these indigenous birds as exclusively (Baker 195 1) or predominantly fruit and seed eaters and occasional insect eaters (Marshall 1949;Marshall 1975;Jenkins 1983;Engbring & Ramsey 1984). Eggs may be an important food for Micronesian Starlings, especially on islands which are small and have simple forest bird and vegetative communities.…”
Section: Emu 90mentioning
confidence: 99%
“…On the island of Tinian, there is also evidence of the bird's prehistoric presence (Steadman 1999); however, a recent detailed mapping of 88 caves revealed no evidence of their presence (Stafford 2003). The few birds observed on the island in the 1940s (Marshall 1949) and 1970s (Pratt et al 1979) may have been infrequent visitors from Saipan or Aguiguan ( J. Reichel and P. Glass, unpubl.…”
mentioning
confidence: 99%